2023
DOI: 10.2147/dddt.s400986
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Dose of Adjuvant Imatinib in Patients with Gastrointestinal Stromal Tumors: Results from a Population Pharmacokinetic Analysis

Abstract: Imatinib is the first-line treatment for patients with gastrointestinal stromal tumors (GIST) after surgery. However, its pharmacokinetic profile varies remarkably between individuals and has not been well characterized in postoperative Chinese patients with GIST. Therefore, this study aimed to develop a population pharmacokinetic (PPK) model and recommend appropriate doses for different patients to achieve the target trough concentration in such a population. Patients and Methods: A total of 110 surgically tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Previous studies had reported the relationship between daily IM dose and IM C min [ 17 , 18 , 34 ], the TDM for IM provided a reference for the adjustment of IM dosage, which added to the utility of TDM in the management of patients with GISTs [ 12 ]. It is worth noting that no foreign studies have previously reported the effect of RBC on imatinib clearance, but a recent domestic study confirmed that RBC had a significant effect on the clearance of IM [ 35 ], which may be due to ethnic differences between domestic and foreign study populations. Thrombocytopenia and neutropenia are common side effects of IM-targeted therapy [ 36 ], which may be why PLT and NEU% are key variables in constructing the model.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had reported the relationship between daily IM dose and IM C min [ 17 , 18 , 34 ], the TDM for IM provided a reference for the adjustment of IM dosage, which added to the utility of TDM in the management of patients with GISTs [ 12 ]. It is worth noting that no foreign studies have previously reported the effect of RBC on imatinib clearance, but a recent domestic study confirmed that RBC had a significant effect on the clearance of IM [ 35 ], which may be due to ethnic differences between domestic and foreign study populations. Thrombocytopenia and neutropenia are common side effects of IM-targeted therapy [ 36 ], which may be why PLT and NEU% are key variables in constructing the model.…”
Section: Discussionmentioning
confidence: 99%